The CLDN5 gene at the blood-brain barrier in health and disease. - Campbell, Matthew (My University, 2023)
The CLDN5 gene encodes claudin-5 (CLDN-5) that is expressed in endothelial cells and forms tight junctions which limit the passive diffusions of ions and solutes. The blood–brain barrier (BBB), composed of brain microvascular endothelial cells and associated pericytes and end-feet of astrocytes, is a physical and biological barrier to maintain the brain microenvironment. The expression of CLDN-5 is tightly regulated in the BBB by other junctional proteins in endothelial cells and by supports from pericytes and astrocytes. The most recent literature clearly shows a compromised BBB with a decline in CLDN-5 expression increasing the risks of developing neuropsychiatric disorders, epilepsy, brain calcification and dementia. The purpose of this review is to summarize the known diseases associated with CLDN-5 expression and function. In the first part of this review, we highlight the recent understanding of how other junctional proteins as well as pericytes and astrocytes maintain CLDN-5 expression in brain endothelial cells. We detail some drugs that can enhance these supports and are being developed or currently in use to treat diseases associated with CLDN-5 decline. We then summarise mutagenesis-based studies which have facilitated a better understanding of the physiological role of the CLDN-5 protein at the BBB and have demonstrated the functional consequences of a recently identified pathogenic CLDN-5 missense mutation from patients with alternating hemiplegia of childhood. This mutation is the first gain-of-function mutation identified in the CLDN gene family with all others representing loss-of-function mutations resulting in mis-localization of CLDN protein and/or attenuated barrier function. Finally, we summarize recent reports about the dosage-dependent effect of CLDN-5 expression on the development of neurological diseases in mice and discuss what cellular supports for CLDN-5 regulation are compromised in the BBB in human diseases.
PUBLISHED
Keywords: Claudin-5; Blood–brain barrier; Tight junction; Psychiatric diseases; Vascular permeability